Compassion and suppression in caregivers: twin masks of tragedy and joy of caring - Emanuele Maria Merlo; Sean M. McNabney; Fabio Frisone; Federica Sicari; Mihai Paunica; Catalina Motofei; Salvatore Settineri (Journal of Mind and Medical Sciences)
Background: Compassionate caregiving is a critical skill for workers among the helping professions, but the degree of empathy required by caregivers can place high demands on their mental and emotional resources. While many professionals employ successful coping strategies to mitigate these stressors, others experience compassion fatigue or burnout from emotional exhaustion. The objective of this research was to evaluate the relationships between caregivers’ demographic/career variables, compassion satisfaction, compassion fatigue, and psychodynamic defense mechanisms such as suppression, repressive function, regression in the service of the Ego, and rationalization. Methods: Participants were 250 caregivers with 178 (71,2%) women and 72 men (28,8%) between 18 and 80 years old (Mean age = 41,37; SD = 13,78). Standardized instruments were used to assess compassion in its different meanings (Professional Quality of Life Measure, ProQOL-5) and deployment of defense mechanisms such as suppression (Suppression Mental Questionnaire, SMQ). Correlational analyses were performed. Results: Greater compassion satisfaction was positively associated with more years of study and inversely associated with increasing age and working days per week. Burnout was positively correlated with greater age, more working hours per week, and more working days per week. Higher secondary traumatic stress was associated with increasing age, higher working hours, and more working days per week, while it was inversely associated with more years of study. Regarding the psychological defense mechanisms, more years of study was inversely associated with lower deployment of the repressive function, regression in the service of the Ego, and rationalization. Advancing age was negatively correlated with repression and regression in the service of the Ego, while it was positively correlated with rationalization. A higher number of working days per week was associated with greater utilization of all defense mechanisms, and higher working hours per week was correlated with higher SMQ total scores and greater use of the repressive function. Greater deployment of nearly all defense mechanisms was associated with greater secondary traumatic stress, while compassion satisfaction was associated with less utilization of repression, rationalization, and lower total SMQ scores. Conclusions: Excessive reliance on psychodynamic defense mechanisms can increase caregivers’ risk for burnout or secondary traumatic stress. Compassion satisfaction might serve as one coping strategy to mitigate emotional exhaustion among professionals.